Pressure Jumps during Drainage in Macroporous Soils. Issue 13 (22nd December 2017) - Soto, Diego; Paradelo, Marcos; Corral, Álvaro; López Periago, José Eugenio
Abstract : Core Ideas: Large pressure jumps occur in macroporous soils during drainage. Jumps result from the fast entrance of a fluid phase into macropores. The entrance occurs after a break in the capillary shield surrounding macropores. Scaling factors of pressure jump sizes may differ from the Haines jumps. Discontinuous air–water displacement at the pore scale (from 10 −5 to 10 −3 m) affects fluid invasion in porous media at the core scale (10 −3 to 1 m). Understanding of this effect is essential to upscale flow processes. In this study we used the analysis of pressure jumps to propose an upscaling mechanism. Large pressure jumps occur during drainage in macroporous structured soils; we suggest a hypothesis for their occurrence. Drainage experiments in packed sand and structured soils enclosing large pores showed large jumps (∼5‐hPa peak pressure). Large jumps resulted from a pressure relaxation process that first initiates from pore‐scale air–water displacements and then expands to larger scales. We found that the power‐law exponents for the distribution of the size of large jumps found in structured soil are greater than the typical values reported for Haines jumps in packed granular porous media. The difference in the exponent suggests that the magnitude of displacements occurring in structured soil has different scaling factors than in simple media. A mechanism for this change of scale is proposed on the basis of the large contrast between pore throat and matrix in macroporous soil. The mechanism consists of a fast pressure relaxation in the macropores triggered by a break in the capillary shield at the pore throat. These findings contribute to an explanation of the scaling relations of air–water displacements in complex porous media and unveil links between the soil structure and flow of fluids.